AB0019 GENETIC POLYMORPHISM OF THE INFLAMMATORY MARKER SAA1 RS12218 (-13 T/C) IS ASSOCIATED WITH AN APTITUDE TO CLINICAL PHENOTYPES OF JUVENILE IDIOPATHIC ARTHRITIS. (13th June 2020) - Fedorov, E.; Salugina, S.; Krylov, M.; Guseva, I.; Samarkina, E.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is one of the most widely-spread immuno-inflammatory diseases of an unknown etiology, the leading manifestation of which is chronic joint inflammation, occuring in children under the age of 16. The disease is a complex of chronic arthropathies with various phenotypic manifestations. Objectives: To verify the hypothesis about the role of SAA1 rs12218 T / C gene polymorphism in the aptitude to various clinical JIA phenotypes. Methods: The study included 132 children, of whom 66 were diagnosed with JIA and 66 were healthy unrelated volunteers (the college students) as a control group, comparable by gender and age. The group of patients with JIA consisted of 44 girls and 22 boys, with an average age of 11.7 ± 4.2 years and an average disease duration of 4.8 ± 3.8 years. The diagnosis and classification of JIA was established according to ILAR-2004 criteria. The JIA group included 30 (45%) patients with oligoarthritis (oJIA), of which 20 patients (67%) were positive for the HLA-B27 antigen (JIA-B27 +) and 10 (33%) patients with anterior uveitis (uJIA); 20 (30%) patients were assigned to the group with the polyarticular variant (pJIA), while all of them were seronegative for the rheumatoid factor; 16 (24%) patients were diagnosed with JIA with a systemic onset (sJIA). The frequencies of the T / C polymorphism of the SAA1 gene were assessed using an allele-specific polymerase chain reaction in a real time mode (RT-PCR). Results: In the group of patients diagnosed with oJIA and (JIA-B27 +), the frequency of the C allele was significantly higher compared to the control (53.3% and 57.5% versus 37.1%, p = 0.035 and 0.022, respectively). No significant differences were detected in the frequencies of the mutant C allele between sJIA and pJIA and the control group. The logistics analysis of the frequency distribution of the alleles of the SAA1 gene demonstrated an increased risk of the C allele in formation of an aptitude to the oJIA variant (OR 1.94, 95% CI 1.00-3.76, p = 0.035). In the oJIA-B27 (+) group, the risk of an aptitude was also increased compared to the control (OR 2.29, 95% CI 1.05-5.04, p = 0.022). Conclusion: The data obtained confirm for the first time the involvement of the rs12218 polymorphism of the SAA1 gene in an aptitude to the oligoarthritis JIA clinical phenotype. The presented results require further replication researches using an enlarged number of patients from different population groups. Disclosure of Interests: None declared